PERANCANGAN PROGRAM APLIKASI INVENTORI PADA PT. SUMBER REJEKI INDOTANI - Hardi Lubis (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
PT.  Sumber Rejeki  Indotani source is a company engaged in the sale of fertilizers. The purpose of this thesis is to create a new inventory system, where the system is used for the provision of information up-to-date information on the brand, type, size, returns and existing inventory in order to become  more effective and efficient.      With the inventory application program is expected to help companies in the processing and storage of data items so that the system can run relatively inventory more effectively and efficiently so as to help improve the performance of the company.      The method used in the design of this app is the SDLC (system development life cycle) which serves to design, analysis, design and implementation. Keywords: System Development Life Cycle (SDLC), Inventory.